21 How fit are paramedics/EMTs? What we know and what should be done?. (26th April 2019) - Ozkaya Senuren, C; Yaylaci, S
Abstract : Background: Emergency Medical Systems (EMS) structures differ across the countries but there is a consensus about the importance of physical performance for the Paramedics/Emergency Medical Technicians (EMTs). However, there is no consensus about the description of their physical workload, its measurement, and evaluation. This systematic review presents the evidence for how the Paramedics/EMTs fitness levels are defined. Method: We searched the following electronic databases: Wiley Online Library, Web of Science, Scopus, Science Direct, EBSCOHost, MEDLINE, Clinical Key and Google Scholar between 2008 and 2019. Search terms related to paramedics, emergency medical technician, and physical fitness. All studies that compared physical performance outcomes included. Results: The review identified twelve full-text publications that matched the inclusion criteria (ten original research article, two systematic reviews), three of the studies investigate the physical performance demands of Paramedics/EMTs, two of them evaluate the health and physical status in current working conditions, six of them describe the risks that they have faced while performing their duties according to their performed work-related tasks and anatomical body parts. Conclusion: Physical performance of Paramedics/EMTs should be evaluated as a whole while several skills were performing simultaneously rather than individual tasks. Especially, there is a need for investigations about fine motor skills and physical performance under the acute fatigue and stress. Therefore, an easily applicable, reliable and validated 24 hour Physical Activity Assesment Questionnaire (24 hour PAAQ) should be developed which results in metabolic equivalent (MET) units to evaluate and defining physical performance requirements and criteria under every circumstance for any EMS structures. Reference: Fischer S. L. et al . (2017). Identifying the critical physical demanding tasks of paramedic work: Towards the development of a physical employment standard. Applied Ergonomics 65, 233–239. Coffey B. et al . (2016). A physical demands description of paramedic work in Canada. International Journal of Industrial Ergonomics 53, 355–362. Karaca, A. & Turnagol, H. H. (2007). Reliability and validity of three different questionnaires in employees. Hacettepe Journal of Sport Sciences 18(2), 68–84. Conflict of interest: None. Funding: None.